Regulation of Triage in Times of a Pandemic: Experiences from Slovenia (and Beyond) - Mišič, Luka; Strban, Grega (Medicine, Law & Society, 2021)
The article offers an overview of legal regulations governing (medical) triage in Slovenia and their importance in times of the Covid-19 epidemic. Focusing on the Patients’ Rights, Health Care and Health Insurance, Medical Services, and Health Services Act, it looks at ways in which legal rules and medical standards intertwine when it comes to deciding who should receive particular limited medical treatment first or in what order. It also deals with ways in which professional rules of conduct or medical standards may, on the one hand, exclude the unlawfulness of particular conduct, and how, on the other hand, law may limit the autonomy of medical practitioners. Both the autonomy in their professional conduct as well as healthcare providers’, but especially professional organizations’ law-making autonomy. Even if grounded in the Slovenian legal order, the present article by nature surpasses its domestic boundaries, since the Covid-19 epidemic created similar issues in several if not in all European jurisdictions. Even more so, since the article addresses several general challenges concerning triage in times or moments of crisis, such as state’s positive obligations, recognition of patients’ private autonomy, medical treatment abroad, ethical deliberations concerning a just distribution of scarce medical services, etc.
Keywords: triage, Covid-19, patients’ rights, human dignity, equal treatment